The idiom ‘Break the bank’ and its transformations in american mass media (a corpora-based analysis) (Eurasian Journal of Philology Science and Education, 2024)
This paper explores the transformative nature of idioms in mass media, focusing on the frequentlyencountered idiom “break the bank” and its transformed version “break the internet”. Examining theidioms through a mixed-methods approach, the research employs quantitative analysis using corporafrom COCA, Google Book Ngram Viewer and dictionaries, along with qualitative methodologies such ascritical discourse analysis and semiotic analysis. The investigation seeks to answer key questions regarding the frequency transformation, emergence and social context of these idioms. The study contributes tofilling gaps in research on transformed idioms in mass media, offering insights into linguistic innovationand digital communication patterns.Furthermore, this paper examines the crucial principles that drive the transformation of idioms inthe digital-time period. By surveying the change from “break the bank”, traditionally linked to financialruin, to “break the internet”, which conveys online popularity, the study highlights how technologicalimprovement and social media advances linguistic creativity. The modified idiom produces big culturalshifts, illustrating how the influence of Internet changes and reshapes language and communicationbetween people. This analysis is not only important in understanding the notion about the idiom evolution but also provides an understanding that the impact of mass media on everyday language can bethoroughly examined and appreciated.Key words: COCA, American English, idiom, transformed idioms, modification, corpus analysis.